Crossed testicular ectopia - Esteves, Edward; Pinus, Jaques; Maranhão, Renato Frota de Albuquerque; Abib, Simone de Campos Vieira; Pinus, José (São Paulo Medical Journal, 1995)
Crossed testicular ectopia (CTE) is a rare anomaly, characterized by migration of one testis towards the opposite inguinal canal. Presented here is a case of crossed ectopia of the right testis, treated by extraperitoneal transposition of the gonad and right orchiopexy. Embriology and surgical findings suggest that CTE is a common consequence of many unclear ethiologic factors, specially mechanical ones, and can be associated with Muller duct persistence. Review of literature suggests a classification of CTE into 3 types: I - associated with inguinal hernia alone; II - associated with persistent mullerian remnants; III - associated with other anomalies without mullerian remnants. Treatment includes transeptal orchiopexy or extraperitoneal transposition of the testis, research for mullerian remnants and other anomalies, and long term postoperative follow-up, due to the risk of becoming malignant.